Making meaning with readers and texts : beginning teachers' meaning-making from classroom events - Edge, Christi U. (Advances in research on teaching ;, 2022)
Connecting the constructs of meaning and experience in the fields of English education, teacher education, literacy and narrative inquiry, Making Meaning with Readers and Texts materializes new insights for advancing teacher education research, broadening understandings of teachers' use of literacy practices for making meaning from classroom events. Exploring new possibilities for framing and reframing learning to teach, Edge advances teacher education research through longitudinal inquiry into beginning teachers' meaning making from classroom events. Novel applications of theory combined with field-based research advances the development of conceptual and practical frameworks for teaching and teacher education. Documenting meaning-making as prospective teachers transition into teaching, extending seminal theories from language arts, reading, and literacy to teacher education, Making Meaning with Readers and Texts advances a new theory for how teachers can fully utilize literacy skills in and for their teaching practices. Reconsidering well-documented problems in preparing teachers and reimagining teaching as reading and composing--curriculum, identity, relationships - Making Meaning with Readers and Texts is crucial reading for teacher educators, English educators, and literacy scholars.